CALCULATION OF THE STANDARD MOLAL THERMODYNAMIC PROPERTIES AS A FUNCTION OF TEMPERATURE AND PRESSURE OF SOME GEOCHEMICALLY IMPORTANT ORGANIC SULFUR COMPOUNDS# - Richard L. (My University, 2001)
The standard molal thermodynamic properties and heat capacity power function coefficients of more than 100 organic sulfur compounds in the crystalline, liquid, and/or gas state have been calculated by combining regressions of experimental data reported in the literature together with carbon number systematics and group additivity algorithms. The compounds for which these calculations have been made include carbon disulfide, branched thiols, cyclic thiols, aromatic thiols, n-alkyl sulfides, branched sulfides, cyclic sulfides (including long-chain n-alkylthiolanes and n-alkylthianes), aromatic sulfides, n-alkyl disulfides, alkylthiophenes, methylated benzothiophenes and dibenzothiophenes, and thianthrene. In addition, the corresponding properties and coefficients for 12 sulfur-containing groups in the crystalline, liquid, and/or gas states have been retrieved, which can be used to estimate the standard molal thermodynamic properties and heat capacity power function coefficients of sulfur-rich kerogens or other high molecular weight organic sulfur compounds of geochemical interest.